Atherogenic Effects of Acute Electronic Cigarette Compared With Tobacco Cigarette Smoking in People Living With HIV: A Randomized Crossover Trial - Theodoros Kelesidis; Leila Fotooh Abadi; Isabelle Ruedisueli; Zoee U. D'Costa; Holly R. Middlekauff (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background People living with HIV (PLWH) are disproportionately affected by tobacco‐related health disparities. Concurrent recreational drug use is also more prevalent. Switching to electronic cigarettes (ECs) has been proposed as a harm reduction strategy. However, it remains unproven whether ECs are less atherogenic than tobacco cigarettes (TCs). Methods and Results PLWH who smoke TCs and met eligibility criteria were invited to enroll in our acute crossover trial (NCT04568395) comparing the effects of using an EC, a TC, and a straw control on different days on monocyte transendothelial migration and monocyte‐derived foam cell formation in our novel ex vivo atherogenesis assay. Twenty‐eight PLWH (aged 41.8±9.8 years; 27 men and 1 woman, 18 with a positive urine toxicology screen) completed all 3 sessions. The acute rise in plasma nicotine was similar after acute TC and EC use (7.32±0.86 ng/mL versus 6.30±0.92 ng/mL, P=0.69). The monocyte transendothelial migration after acutely smoking a TC increased by a mean of 0.65‐fold difference compared with the straw control (P<0.01). The monocyte transendothelial migration after using an EC was not significantly increased compared with the straw control. The monocyte‐derived foam cell formation after acutely smoking a TC was increased by a mean of 0.65‐fold difference compared with the straw control (P<0.001). The monocyte‐derived foam cell formation after acutely using an EC was not significantly increased compared with the straw control. These findings were present in PLWH with and without concurrent recreational drug use. Conclusion These data suggest smaller proatherogenic effects following EC versus TC use in PLWH and justify a larger study looking at cardiovascular risks of ECs in PLWH who smoke, including those who use recreational drugs, populations disproportionately affected by tobacco‐related health disparities.